Citrus sudachi Peel Extract Suppresses Cell Proliferation and Promotes the Differentiation of Keratinocytes through Inhibition of the EGFR–ERK Signaling Pathway - Shogo Abe; Misako Ueno; Mami Nishitani; Tetsuya Akamatsu; Takumi Sato; Marie Shimoda; Hiroki Kanaoka; Yoshitaka Nii; Hiroko Yamasaki; Keizo Yuasa (Biomolecules, 2020)
Citrus sudachi is a well-known fruit in Tokushima Prefecture, Japan, and its peels are rich in phytochemicals, including phenolic compounds. Although it is expected that the extract of the C. sudachi peel elicits various beneficial physiological activities, the effect on the skin has not been investigated. In this study, we report that the aqueous extract from the peel of C. sudachi suppresses cell proliferation of the immortalized human keratinocyte cell line, HaCaT, and primary normal human epidermal keratinocytes. The extract of C. sudachi peel suppressed epidermal growth factor (EGF)-induced EGF receptor activation and tumor necrosis factor (TNF)-α-induced extracellular regulated kinase (ERK) 1/2 activation, which suggests that the extract exerts its inhibitory effect through inhibition of both the EGF receptor (EGFR) and its downstream molecules. Additionally, the extract of C. sudachi peel potentiated calcium-induced keratinocyte differentiation. These results suggest that the extract of C. sudachi peel may have beneficial effects against skin diseases that are characterized by hyperproliferation of epidermal keratinocytes, such as those seen in psoriasis and in cutaneous squamous cell carcinoma.